Cutting and germination of Eugenia involucrata seeds (Revista de Ciências Agroveterinárias, 2016)
The objective of this study is to verify the cutting efficiency of Eugenia involucrata seeds in seedling formation, as a way to maximize seed lots for sapling production. E. involucrata seeds were submitted to the following treatments: a) Control (uncutting seeds), b) Seeds transversely cut, with or without hilum, c) Seeds longitudinally cut, with and without hilum and germinated afterwards on germitest paper roll substrate at a temperature of 25 ° C and constant white light, with four repetitions of 25 seeds or seed fractions. The percentage of propagules with capacity to produce normal seedlings (the germination percentage) and germination speed (the Speed of Germination Index) were calculated. The uncut seeds (control) showed a higher germination percentage (72%) and speed (SGI = 0.64). The use of seed fractions was not considered an efficient method for maximizing E. involucrata seed lots, since germination was directly affected.
Keywords: Propagules; maximizing germination; seedling production.